Frequency of Various Macroscopic Placental Pathologies in Patients with Intrauterine Growth Retarded Baby with Preeclampsia - Ajmal, Diya; Sabir, Samina Aliya; Ayesha; Amjad, Ayesha (Indus Journal of Bioscience Research, 2025)
Background: Intrauterine growth retardation is a common condition with the main etiology of placental insufficiency, leading to low birth weight and long-term health implications. Placental pathology is the main cause and is detectable by gross examination. Objectives: To determine frequency of various macroscopic placental pathologies in patients with intrauterine growth retarded baby with preeclampsia. Study design: Cross-sectional study. Place and duration of study: Lady Reading Hospital, Peshawar from October-2024 to March-2025. Methods: A total of 140 women who gave birth to intrauterine growth retorted baby with preeclampsia were included. After the delivery of placenta, placenta was examined thoroughly for gross morphological features to assess for macroscopic pathologies of placenta related to intrauterine growth retardation of the baby. Frequency of these macroscopic pathologies was stratified by age, weeks of gestation and cause of IUGR and post-stratification comparison was performed by using Chi-square test. Results: Median age of the mother was 25.00 (8.00) years. Median weight of the baby was 2.10 (0.30) kg. Most common cause of intrauterine growth retardation was maternal anemia found in 67 (47.90%). Amongst all IUGR cases, placenta was macroscopically normal in 11 (7.90%) patients while there were macroscopic pathologies on placenta in 129 (92.10%) patients. Amongst these patients (n = 129), most common macroscopic pathology was two vessel umbilical cord found in 38 (29.47%) cases followed by eccentric attachment site of umbilical cord in 35 (27.13%) cases. Conclusion: In cases of intrauterine growth retardation macroscopic placental pathologies are common and were observed in 92.10% cases.